The Representation of Media Power in Editorial Languages on Pikiran Rakyat Daily Newspaper - Rahzanie, Risha Devina; Rustono, Rustono (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
The title of the Plan becomes a media that describes editorial powers in expressing their opinions. This study aims to analyze the representation of power as reflected in the editorial on terrorism-themed articles in the Pikiran Rakyat General Daily with the article title "Terror Terror." This research is qualitative research using descriptive qualitative study methods. The research data were analyzed using the critical discourse analysis of Teun A van Dijk. The data collection technique used in this study was the skillful listening free technique. The results of this study are in the form of representation of editorial powers in the editorial on the theme of terrorism, namely the editorial alignments of the police and terrorism which are explicitly displayed. The editors positively imaged the police in this editorial. The editors negatively imaged terrorism in this editorial.